CHINESE INDONESIANS: CHINESE MUSLIMS AND THE COLLAPSE OF THE BUSINESS REPUBLIC JAKARTA: REPUBLIKA - Teguh Setiawan; Reviewed by: Cucu Nurjamilah (Graduate Program of Pontianak Institute of Islamic Studies, 2013)
This book written by Teguh Setiawan and published by Republika is very interesting to read because from it the reader will get a lot of information about the ethnic Chinese in Indonesia, among them: the greatness of the Chinese Muslim leaders and bad luck of Chinese Muslim community during the Dutch colonial period and the heyday of the Muslim ethnic Chinese in Indonesia, and portrait of the Chinese Muslims from the past. In addition, readers will be interested in doing research on other ethnic Chinese, perhaps even you would like to know the ethnic Chinese in the rural areas recounted in the book.